2012
DOI: 10.1111/j.1467-9396.2012.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

How Does Foreign Direct Investment Really Affect Developing Countries' Growth?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 51 publications
13
126
1
12
Order By: Relevance
“…12; impact for example on an underdeveloped or still developing country would be expected larger when more FDI is invested and capitalized in the country, whereas it is not expected to add much for already developed country when compared to the former. Herzer (2012) argues that the effect of FDI varies across countries, and that this variation is mainly explained by cross -country differences in freedom from government intervention, business freedom, and export dependence (Herzer, 2012). Therefore, it is obviously arguable whether FDI inflows is the same across countries.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…12; impact for example on an underdeveloped or still developing country would be expected larger when more FDI is invested and capitalized in the country, whereas it is not expected to add much for already developed country when compared to the former. Herzer (2012) argues that the effect of FDI varies across countries, and that this variation is mainly explained by cross -country differences in freedom from government intervention, business freedom, and export dependence (Herzer, 2012). Therefore, it is obviously arguable whether FDI inflows is the same across countries.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…As shown in Albuquerque (2003), the share of FDI in total foreign equity flows is larger for developing countries than for developed countries, an empirical regularity explained by Goldstein and Razin (2006) with the high production costs in developed economies which imply that it is more beneficial to incur the fixed costs associated with FDI in developing countries than in developed ones. As FDI flows have become an important and often dominant source of finance in developing countries, concerns have grown that economic growth and macroeconomic stability might be harmed in countries exposed to extreme fluctuations of these flows (Lensink and Morrissey 2006;Herzer 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, much research in the sociology of development, adopting world-systems and dependency theoretical lenses points to negative consequences of foreign investment (Dixon & Boswell 1996;Kentor 1998Kentor , 2001de Soysa & Oneal 1999;Alderson & Nielsen 2002;Beer & Boswell 2002;Alderson 2004;Mahutga & Bandelj 2008). Further, recent studies on the link between FDI and growth have actually found a negative relationship (Herzer 2012;Curwin & Mahutga 2014). All this considered, neoliberalism that promotes FDI as a growth strategy is treated here not as based on objective economic relationships but as a policy paradigm that is constructed as more or less legitimate by states that embrace the Washington Consensus (Fourcade & Babb 2002;Mudge 2008).…”
Section: The Interplay Of Neoliberal Globalisation and Postsocialist mentioning
confidence: 99%
“…874 investors to participate by bidding in contests for the purchase of state owned enterprises involving both domestic and foreign actors. This resulted in foreign-led economies (Bohle & Greskovits 2007, 2012Drahokoupil 2008b).…”
Section: The Interplay Of Neoliberal Globalisation and Postsocialist mentioning
confidence: 99%
See 1 more Smart Citation